Pendampingan Pencatatan Keuangan dan Digital Marketing pada UMKM Pemotongan Ayam Pak Joko - Siti Kholifatun; Tutut Dewi Astuti (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service activity was motivated by the still low ability of business owners to maintain financial records and digital promotions. Pak Joko Chicken Slaughterhouse is one of the MSMEs experiencing challenges in financial management due to its manual system and lack of use of digital media for business promotion. The objective of this activity was to improve managerial capacity through Microsoft Excel-based digital bookkeeping training and online marketing training with Google Maps and Instagram. The method used was a participatory approach through three stages of activities: field surveys, training, and evaluation of results. The results of the activity showed an increase in partners' understanding and skills in maintaining more structured and accurate financial records using Excel. Partners also succeeded in creating business profiles on Google Maps and business Instagram accounts used to promote products digitally. The tangible impact of this activity is increased awareness of the importance of financial records and digital promotions, as well as increased business competitiveness. In conclusion, digital bookkeeping and digital marketing training has proven effective in driving the transformation of traditional businesses to modern, technology-based management.